An optofluidic approach for gold nanoprobes based-cancer theranostics - Panwar, Nishtha (2018)
Suppression of overexpressed gene mutations in cancer cells through RNA interference (RNAi) technique is a therapeutically effective modality for oncogene silencing. In general, transfection agent is needed for siRNA delivery. Also, it is a tedious and time consuming process to analyze the gene transfection using current conventional flow cytometry systems and commercially available transfection kits. Therefore, there are two urgent challenges that we need to address for understanding and real time monitoring the delivery of siRNA to cancer cells more effectively. One, nontoxic, biocompatible and stable non-viral transfection agents need to be developed and investigated for gene delivery in cancer cells. Two, new, portable optofluidic methods need to be engineered for determining the transfection efficiency of the nanoformulation in real time. First, we demonstrate the feasibility of using gold nanorods (AuNRs) as nanoprobes for the delivery of Interleukin-8 (IL-8) siRNA in a pancreatic cancer cell line- MiaPaCa-2. An optimum ratio of 10:1 for the AuNRs–siRNA nanoformulation required for efficient loading has been experimentally determined. Promising transfection rates (≈88%) of the nanoprobe-assisted gene delivery are quantified by flow cytometry and fluorescence imaging, which are higher than the commercial control, Oligofectamine. The excellent gene knockdown performance (over 81%) of the proposed model support in vivo trials for RNAi-based cancer theranostics. In addition to cancer theranostics, our nanoprobe combination can be also applied for disease outbreak monitoring like MERS. Second, we present an optical fiber-integrated microfluidic chip that utilizes simple hydrodynamic and optical setups for miniaturized on-chip flow cytometry. The chip provides a powerful and convenient tool to quantitatively determine the siRNA transfection into cancer cells without using bulky flow cytometer. These studies outline the role of AuNRs as potential non-viral gene delivery vehicles, and their suitability for microfluidics-based lab-on-chip flow cytometry applications.